2018
DOI: 10.1002/qj.3309
|View full text |Cite
|
Sign up to set email alerts
|

An objective global climatology of polar lows based on reanalysis data

Abstract: Here we present an objective global climatology of polar lows. In order to obtain objective detection criteria, the efficacy of several parameters for separating polar lows

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
120
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(148 citation statements)
references
References 36 publications
11
120
4
Order By: Relevance
“…Regardless, Stoll et al . () found that the 10 m wind speed was not very effective at identifying polar lows. As a measure of intensity we use the maximum relative vorticity (at 925 hPa) for each polar low track, but no threshold is applied to this quantity.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…Regardless, Stoll et al . () found that the 10 m wind speed was not very effective at identifying polar lows. As a measure of intensity we use the maximum relative vorticity (at 925 hPa) for each polar low track, but no threshold is applied to this quantity.…”
Section: Methodsmentioning
confidence: 96%
“…For this we use a box of 132 × 132 km (11 × 11 grid cells), similar to the 2° latitude radius used by Stoll et al . (). It should be noted that the wind speed threshold in the definition is based on observations, while modelled 10 m wind speed is a diagnostic field which is often subject to tuning.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The preferred region for cyclogenesis is generally where both a strong temperature gradient and an upper-level trough are found (e.g., Davies, 1997;Shimada et al, 2014;Uccellini, 1990). Around Antarctica, the strongest temperature gradient is found along the fringes of the ice pack, making the sea ice edge a preferred region for cyclogenesis (e.g., Schlosser et al, 2011;Stoll et al, 2018;Yanase & Niino, 2007). High baroclinic instability associated with the horizontal temperature gradient is crucial for the formation and the intensification of the cyclones (Davies, 1997;Uccellini, 1990;Yanase & Niino, 2007), but cyclogenesis occurs only at the entrance and exit regions of upper-level troughs (e.g., Kolstad, 2011;Shimada et al, 2014).…”
Section: Introductionmentioning
confidence: 99%